PERTUMBUHAN DAN KETIMPANGAN (SUATU TINJAUAN HYPHOTHESIS KUZNET) - Emi Suwarni; Mardalena Mardalena (Department of Development Economics, Universitas Sriwijaya, 2011)
The impact of economic growth upon the poor in developing countries is complex and contentious. Does growth benefit in asociety all, and how does it affect inequality and vulnerability? There is profound disagreement about relationship between growth and distribution in academic circles. A number of cross sectional studies verify the inverted-U hypothesis and illustrate that in low-income countries inequality is negatively and robustly correlated with growth . In contrast, several studies ultilizing data on individual country across time cast doubt the validity of the inverted-U hypothesis. There has been a debate about links between growth, distribution and poverty.Keywords: growth, inequality, poverty